Microstructure and Corrosion Studies on Different Zones of Super Duplex Stainless Steel UNS S32750 Weldment - Han, Yongdian; Zhang, Yankun; Jing, Hongyang; Gao, Zhanqi; Xu, Lianyong; Zhang, Zhiqiang; Zhao, Lei (Frontiers in Materials, 2020)
The influences of microstructure and elemental distribution on pitting corrosion resistance and passive film in different regions of a super duplex stainless steel welded joint were investigated. The banded microstructure disappeared after welding and transformed to the coarse equiaxed ferrite grains in the heat-affected zone. Three types of austenitic microstructure formed in the weld center, only two types occurred in the weld cap and weld root. It is found that the elements Ni and N were enriched in austenite, while Cr and Mo were concentrated in the ferrite. The Cr2N was found precipitating in some specific regions with a lower austenite content, which led to the relatively poorer resistance to pitting corrosion in the heat-affected zone, weld root, and weld cap. The ferrite observed in each studied region of the joint was prone to experiencing selective corrosion due to its lower pitting resistance equivalent number. The content of Cr in the region around the Cr2N disappeared, so that Cr-depletion was formed as the original location of pitting. The electrochemical impedance spectroscopy results also showed that no difference exists in the passive film structure in all of the regions of the joint, and regular banded microstructure was helpful to the passive film.